Exponential Fit to Food Degradation Experiment (JOURNAL OF ADVANCES IN MATHEMATICS, 2023)
Students in the Principles of Biology I course use a lot of course time preparing solutions each week in their coursebased research experience. This experiment was designed to determine the degradation rates of prepared solutions ofvarious plant-based foods (i.e., Napa cabbage, rice, peanuts, and apple) under refrigeration as a means of reducing theamount of time for solution preparation. Scaling from the original lab procedures, approximately sixty milliliters offiltrate were prepared from the listed foods and testing was conducted on a thrice-weekly schedule. The concentrationof proteins and carbohydrates were measured using the Bradford’s assay and Benedict’s test, respectively. The datarevealed a noticeable trend in degradation in protein for all the samples. The rice sample proved to be an outlier witha marked increase in reducing sugars, while the other samples gradually decreased.